Sewing Success? Employment, Wages, and Poverty following the End of the Multi-Fibre Arrangement - Lopez-Acevedo, Gladys; Robertson, Raymond (Washington, DC: World Bank, 2013)
The global textile and apparel sector is critically important as an early phase in industrialization for many developing countries and as a provider of employment opportunities to thousands of low-income workers, many of them women. The goal of this book is to explore how the lifting of the Multi-fibre Arrangement/ Agreement on Textiles and Clothing (MFA/ATC) quotas has affected nine countries Bangladesh, Cambodia, Honduras, India, Mexico, Morocco, Pakistan, Sri Lanka, and Vietnam with the broader aim of better understanding the links between globalization and poverty in the developing world. Analyzing how employment, wage premiums, and the structure of the apparel industry have changed after the MFA/ATC can generate important lessons for policy makers for economic development and poverty reduction. This book uses in-depth country case studies as the broad methodological approach. In-depth country studies are important because countries are idiosyncratic: differences in regulatory context, history, location, trade relationships, and policies shape both the apparel sector and how the apparel sector changed after the end of the MFA. In-depth country studies place broader empirical work in context and strengthen the conclusions. The countries in this book were chosen because they represent the diversity of global apparel production, including differences across regions, income levels, trade relationships, and policies. The countries occupy different places in the global value chain that now characterizes apparel production. Not surprisingly, the countries studied in this book represent the diversity of post-MFA experiences. This book highlights four key findings: The first is that employment and export patterns after the MFA/ATC did not necessarily match predictions. This book shows that only about a third of the variation in cross-country changes in exports is explained by wage differences. While wage differences explain some of the production shifts, domestic policies targeting the apparel sector, ownership type, and functional upgrading of the industry also played an important role. Second, changes in exports are usually, but not always, good indicators of what happens to wages and employment. While rising apparel exports correlated with rising wages and employment in the large Asian countries, rising exports coincided with falling employment in Sri Lanka. Third, this book identifies the specific ways that changes in the global apparel market affected worker earnings, thus helping to explain impacts on poverty. Fourth, in terms of policies, the countries that had larger increases in apparel exports were those that promoted apparel sector upgrading; those that did not promote upgrading had smaller increases or even falling exports.